Dialogar com a dança - Sasportes, José (2016)
The art of dance has been judged futile and dangerously sensuous. For those reasons it has been persecuted, but it also has had its advocates. First among them, Luciano, who wrote in Greek The Art of Dance, a dialogue between a supporter of dance and an enemy, who ends up converted to dance. In the Renaissance the text was translated into Latin, and since then it inspired further reflexions on the matter, also in dialogue form. Two topics from Luciano were repeated throughout the centuries: the dignity of dance and the opposition between dramatic dance and pure dance. This paper engages in the illustration of the permanence of arguments taken from Luciano until the twentieth century.